Statistical analysis of storm electrical discharges reconstituted from a lightning mapping system, a lightning location system, and an acoustic array. Issue 8 (26th April 2016) - Gallin, Louis‐Jonardan; Farges, Thomas; Marchiano, Régis; Coulouvrat, François; Defer, Eric; Rison, William; Schulz, Wolfgang; Nuret, Mathieu
Abstract: In the framework of the European Hydrological Cycle in the Mediterranean Experiment project, a field campaign devoted to the study of electrical activity during storms took place in the south of France in 2012. An acoustic station composed of four microphones and four microbarometers was deployed within the coverage of a Lightning Mapping Array network. On the 26 October 2012, a thunderstorm passed just over the acoustic station. Fifty‐six natural thunder events, due to cloud‐to‐ground and intracloud flashes, were recorded. This paper studies the acoustic reconstruction, in the low frequency range from 1 to 40 Hz, of the recorded flashes and their comparison with detections from electromagnetic networks. Concurrent detections from the European Cooperation for Lightning Detection lightning location system were also used. Some case studies show clearly that acoustic signal from thunder comes from the return stroke but also from the horizontal discharges which occur inside the clouds. The huge amount of observation data leads to a statistical analysis of lightning discharges acoustically recorded. Especially, the distributions of altitudes of reconstructed acoustic detections are explored in detail. The impact of the distance to the source on these distributions is established. The capacity of the acoustic method to describe precisely the lower part of nearby cloud‐to‐ground discharges, where the Lightning Mapping Array network is not effective, is also highlighted. Key Points: Natural lightning has successfully been reconstructed with a software used in infrasound research There is a good statistical fit between acoustic detections and VHF detections There is a good agreement between acoustic and VLF detections for lower sections of flashes